2011
DOI: 10.1016/j.canlet.2011.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester (CAPE), derived from a honeybee product propolis, exhibits a diversity of anti-tumor effects in pre-clinical models of human breast cancer

Abstract: Breast cancer (BC) patients use alternative and natural remedies more than patients with other malignancies. Specifically, 63%–83% use at least one type of alternative medicine and 25%–63% use herbals and vitamins. Propolis is a naturopathic honeybee product, and CAPE (caffeic acid phenethyl ester), is a major medicinal component of propolis. CAPE, in a concentration dependent fashion, inhibits MCF-7 (hormone receptor positive, HR+) and MDA-231 (a model of triple-negative BC (TNBC) tumor growth, both in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
139
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(152 citation statements)
references
References 55 publications
(55 reference statements)
10
139
1
2
Order By: Relevance
“…Bioactive compounds and phytochemicals from plants have been shown to suppress early and late stages of carcinogenesis and can consequently inhibit proliferation of malignant cancer cells (23)(24)(25). In the present study, we showed that genipin efficiently inhibited the growth of MDA-MB-231 human breast cancer cells.…”
Section: Discussionsupporting
confidence: 58%
“…Bioactive compounds and phytochemicals from plants have been shown to suppress early and late stages of carcinogenesis and can consequently inhibit proliferation of malignant cancer cells (23)(24)(25). In the present study, we showed that genipin efficiently inhibited the growth of MDA-MB-231 human breast cancer cells.…”
Section: Discussionsupporting
confidence: 58%
“…We have previously described that CAPE, the major active component of propolis, induces a diversity of anti-tumor effects in ER+ and ER-breast cancer [25,26]. Here, we compared propolis with CAPE alone to determine whether CAPE's effects were intact in the natural product.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that CAPE inhibits growth of breast cancer cells and breast cancer stem cells, induces cell cycle arrest and apoptosis, and suppresses angiogenesis. Gene arrays showed that CAPE causes extensive changes in gene expression in both ER+ and ER-types of breast cancer cells including the inhibition of NF-κB [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAPE is chemopreventive against intestinal, colon and skin cancer, and also has been shown to decreases the formation of preneoplastic hepatic lesions when is administrated in a rat model of liver carcinogenesis [19][20][21], but the mechanism of these properties is not completely understood. Recently, CAPE, in a concentration dependent fashion, was shown to inhibit MCF-7 (hormone receptor positive, HR+) and MDA-MB-231 (a model of triple negative BC (TNBC)) tumor growth, either in vitro or in vivo without much effect on normal mammary cells [22]. At the same time, CAPE was found to cause pronounced changes in bCSC characteristics manifested by inhibition of self renewal, progenitor formation, clonal growth in soft agar, and concurrent significant decrease in CD44 content, all signs of decreased malignancy potential [23].…”
Section: Active Compounds In Propolismentioning
confidence: 99%